M2‐like tumor‐associated macrophages promote epithelial–mesenchymal transition through the transforming growth factor β/Smad/zinc finger e‐box binding homeobox pathway with increased metastatic potential and tumor cell proliferation in lung squamous cell carcinoma - Sumitomo, Ryota; Menju, Toshi; Shimazu, Yumeta; Toyazaki, Toshiya; Chiba, Naohisa; Miyamoto, Hideaki; Hirayama, Yutaka; Nishikawa, Shigeto; Tanaka, Satona; Yutaka, Yojiro; Yamada, Yoshito; Nakajima, Daisuke; et al. (Cancer science, 2023)
Epithelial‑mesenchymal transition (EMT) promotes primary tumor progression toward a metastatic state. The role of tumor‐associated macrophages (TAMs) in inducing EMT in lung squamous cell carcinoma (LUSC) remains unclear. We aimed to clarify the significance of TAMs in relation to EMT in LUSC. We collected 221 LUSC specimens from patients who had undergone surgery. Immunohistochemistry was performed to evaluate M1‐like and M2‐like TAM distribution and EMT by E‐cadherin and vimentin staining. Human LUSC cell lines (H226 and EBC‐1) and a human monocyte cell line (THP‐1) were used for in vitro experiments. M2‐like polarization of TAMs and EMT marker expression in LUSC cells were evaluated by western blotting. The biological behavior of LUSC cells was evaluated by migration, invasion, and cell proliferation assays. Immunohistochemical analysis showed that 166 (75.1%) tumors were E‐cadherin‐positive and 44 (19.9%) were vimentin‐positive. M2‐like TAM density in the tumor stroma was significantly associated with vimentin positivity and worse overall survival. Western blotting demonstrated higher levels of CD163, CD206, vascular endothelial growth factor, and transforming growth factor beta 1 (TGF‐β1) in TAMs versus unstimulated macrophages. Furthermore, increased TGF‐β1 secretion from TAMs was confirmed by ELISA. TAM‐co‐cultured H226 and EBC‐1 cells exhibited EMT (decreased E‐cadherin, increased vimentin). Regarding EMT‐activating transcriptional factors, phosphorylated Smad3 and ZEB‐family proteins were higher in TAM‐co‐cultured LUSC cells than in parental cells. TAM‐co‐cultured H226 and EBC‐1 cells demonstrated enhanced migration and invasion capabilities and improved proliferation. Overall, the present study suggests that TAMs can induce EMT with increased metastatic potential and tumor cell proliferation in LUSC. TAM‐co‐cultured LUSC cells exhibited EMT through the TGF‐beta/Smad/ZEB pathway. TAM‐co‐cultured LUSC cells demonstrated enhanced migration and invasion capabilities and increased tumor cell proliferation.